2010
DOI: 10.1007/s11250-010-9694-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of chicken embryo-adapted fowl adenovirus serotype 4 vaccine in broiler chickens

Abstract: The current study was planned to develop an efficient vaccine against hydropericardium syndrome virus (HSV). Currently, formalin-inactivated liver organ vaccines failed to protect the Pakistan broiler industry from this destructive disease of economic importance. A field isolate of the pathogenic hydropericardium syndrome virus was adapted to chicken embryos after four blind passages. The chicken embryo-adapted virus was further serially passaged (12 times) to get complete attenuation. Groups of broiler chicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
37
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 30 publications
(40 reference statements)
8
37
1
1
Order By: Relevance
“…This vaccine has many drawbacks, including (1) unpredictable immune response provoked by the vaccine, (2) impurity and the vaccine may contains other viruses and bacteria (Mansoor et al, 2010). The above results revealed that the lyophilized live attenuated vaccine was safer, immunogenic and easy to administer.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This vaccine has many drawbacks, including (1) unpredictable immune response provoked by the vaccine, (2) impurity and the vaccine may contains other viruses and bacteria (Mansoor et al, 2010). The above results revealed that the lyophilized live attenuated vaccine was safer, immunogenic and easy to administer.…”
Section: Discussionmentioning
confidence: 91%
“…All the prepared vaccines were tested for sterility on different microbiological media. The stability of the vaccines was also checked before administration to birds (Mansoor et al, 2010).…”
Section: Preparation Of Vaccinesmentioning
confidence: 99%
“…No chicks died in the KR5 strain infected group while the mortality with the field isolates was up to 100% (Mazaheri et al, 1998). Moreover, effective oil emulsion vaccines have been introduced in breeder and broiler flocks for disease prevention and control (Mansoor et al, 2011;Kim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…HHS associated losses could be reduced by vaccination. Inactivated liver homogenates from infected chickens, and inactivated virus propagated in cell culture and/or embryonated eggs based vaccines are available, however they provide only variable protection [6,25]. Recently, Schonewille et al (2010) reported live FAdV-4 vaccine, but with lack of neutralizing antibodies.…”
Section: Introductionmentioning
confidence: 99%